Toxicologic Pathology Study of uranyl acetate by oral intubation on Sprague – Dawelly Rats. - Majeed, Saleh K.; Falih, Inam B.; AL-Shammary, Basam F. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Urany1 acetate (UA) mostly a kidney poison or chemical toxic and not nearly so much radiological also is not accumulative toxic, so it is not concentrated in the food chain nor would it cause pathological condition due to increase levels from expomers. Therefore, the study aimed to detect the target organ as most of the lethal dose (LD50) male rats died within 24 hours. Methods: Study was done on (120) male rats of 2 months old, at varying dosage level of uranyl acetate ranging from LD 50 of 2.5 and 1.5gm/kg and varying dosage level, by oral intubation. There were (40) rats for LD 50 were given single oral dose from 2.5 to 1.5 gm /kg every day. Eighty rats for the main study, (20) rats each group as intermediate, low and high dose. After LD 50, the trail was done on groups of rats, starting as high dose as 150 mg / kg day by day then followed by intermediate dose 100 mg / kg and low dose level 75 mg / kg b.w every other day respectively with control untreated group. Duration of the study (55 day) on all rats were killed and followed by histopathological examination. Results: The histopathological changes ranged from sever necrosis of the proximal convoluted tubules result in renal failure and that was mainly at the LD 50 and maximum level dose, rats either died after few hours or live for few days. Showing arched back and killed in poor condition, while rats treated with intermediate and low dose level showed less sever changes, mostly as dilated cortical tubules and / or cortical tubular basophilia, , only with occasional cortical tubular necrosis . Conclusion: The Present study showed that the kidney, proximal convoluted tubules, the target for toxicological pathology of heavy metal and the main cause of death was renal failure in sever morbid cases.